The Dimensions of Black Women’s Learning in the Environmental Justice Movement in the Southeastern U.S. - Tuere A. Bowles (Adult Education Research Conference, 2007)
This qualitative research study explored black women’s learning in social action. Data analysis revealed that black women's informal learning in the environmental justice movement, specifically, is shaped by: mentoring relationships, individual and collective experiences, and intergenerational learning.